DOI: 10.18297/etd/1034
|View full text |Cite
|
Sign up to set email alerts
|

Learning from graphically integrated 2D and 3D representations improves retention of neuroanatomy.

Abstract: Visualizations in the form of computer-based learning environments are highly encouraged in science education, especially for teaching spatial material. Some spatial material, such as sectional neuroanatomy, is very challenging to learn. It involves learning the two dimensional (2D) representations that are sampled from the three dimensional (3D) object. In this study, a computer-based learning environment was used to explore the hypothesis that learning sectional neuroanatomy from a graphically integrated 2D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 54 publications
1
11
0
1
Order By: Relevance
“…First, Fritz et al () did not find significant differences in overall, factual and spatial scores between long‐term and short‐term groups. Second, Naaz () reported significant positive results in favor of the integrated 2D‐3D imaging over the sequential 2D‐3D approach on spatial means ( P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…First, Fritz et al () did not find significant differences in overall, factual and spatial scores between long‐term and short‐term groups. Second, Naaz () reported significant positive results in favor of the integrated 2D‐3D imaging over the sequential 2D‐3D approach on spatial means ( P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported results on factual means from comparisons between 3DVT interventions; Tam et al () tested guided 3D CT images versus self‐learned 3D CT images and found no significant difference between the two interventions ( P = 0.52). Naaz () found no differences between sequential 2D‐3D and integrated 2D‐3D interventions on spatial means in teaching brain anatomy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations